2020
DOI: 10.1136/bmjopen-2020-040413
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mass testing for control of COVID-19: a systematic review protocol

Abstract: IntroductionSince March 2020, when the COVID-19 outbreak has been deemed a pandemic by the WHO, the SARS-CoV-2 spreading has been the focus of attention of scientists, authorities, public health agencies and communities around the world. One of the great concerns and challenges, mainly in low-income and middle-income countries, is the identification and monitoring of COVID-19 cases. The large-scale availability of testing is a fundamental aspect of COVID-19 control, but it is currently the biggest challenge fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 35 publications
0
39
0
4
Order By: Relevance
“…Initially, the existence of controlled descriptors (such as MeSH terms, CINAHL headings, PsycINFO thesaurus, and DeCS-Health Science Descriptors) and their synonyms (keywords) was verified in each database. We combined the search terms using the Boolean operators “AND” and “OR.” 37 38 39 Subsequently, we used a search strategy combining MeSH terms and free text words (eg, “(child OR child, hospitalized OR adolescent OR adolescent, hospitalized OR paediatrics) AND (clown doctors OR clown intervention OR clowns OR therapeutic clown OR clowns in hospital OR hospital clowns) AND (symptoms OR affective symptoms OR behavioural symptoms OR symptom clusters OR clusters of neuropsychological symptoms OR neuropsychological symptoms OR anxiety OR stress, psychological OR distress OR psychological impact)”).…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the existence of controlled descriptors (such as MeSH terms, CINAHL headings, PsycINFO thesaurus, and DeCS-Health Science Descriptors) and their synonyms (keywords) was verified in each database. We combined the search terms using the Boolean operators “AND” and “OR.” 37 38 39 Subsequently, we used a search strategy combining MeSH terms and free text words (eg, “(child OR child, hospitalized OR adolescent OR adolescent, hospitalized OR paediatrics) AND (clown doctors OR clown intervention OR clowns OR therapeutic clown OR clowns in hospital OR hospital clowns) AND (symptoms OR affective symptoms OR behavioural symptoms OR symptom clusters OR clusters of neuropsychological symptoms OR neuropsychological symptoms OR anxiety OR stress, psychological OR distress OR psychological impact)”).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Gelfand et al [22], found that countries with both efficient governments and high tightness scores were more effective in reducing the spread of COVID-19 and reducing mortality rates. In this paper, we focus on the early dynamics of the pandemic, where inadequate and heterogeneous testing capacities are as, if not more, important in driving epidemic dynamics than geospatial differences [23]. This allows us to test for a wide-range of potential correlates-testing, intervention, population density, behavior, etc.-all potentially driving early reported data.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22] Few studies have quantified how the efficiency of testing and contact tracing limits disease spread. Lopes-Júnior et al 23 published a protocol to evaluate the influence of testing capacity for symptomatic individuals on the control of COVID-19. We referred to this protocol and searched PubMed and Google Scholar in our literature review for studies evaluating the effect of testing and contact tracing through March 2021.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%